Bridging Language Barriers: An Exploration of Eminem's Song Translation Methods from English to Indonesian - Razi, Ivan Muhammad; Retnomurti, Ayu Bandu (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2022)
The aim of this article is to explain the process of translating Eminem's song titles and the various translation methods used to produce translations that are accurate and acceptable. The research methodology employed in this work is descriptive qualitative research, using a comparative approach. The article outlines the challenges involved in translating English songs into Indonesian while maintaining the melody and using limited words. The researcher used Newmark's translation theory as a framework for the translation process. The study utilized six types of translations, including word-for-word, faithful, free, semantic, idiomatic, communicative, adaptation, and literal. The most frequently used method was the word-for-word translation (53.9%), followed by faithful translation (30.7%). There were no instances of idiomatic, communicative, adaptation, or literal translations.